Logistic Decisions in the Installation of Offshore Wind Farms: A Conceptual Framework - Mario O. A. González; Gabriela Nascimento; Dylan Jones; Negar Akbari; Andressa Santiso; David Melo; Rafael Vasconcelos; Monalisa Godeiro; Luana Nogueira; Mariana Almeida; Pedro Oprime (Energies, 2024)
Offshore wind energy has achieved significant reductions in its levelized cost of energy (LCoE) in the past decade, but still needs efficiency improvements. Approximately 18% of the LCoE is related to logistical costs, underscoring the need for optimization in this area. Despite its importance, logistical decisions during offshore wind farm installations remain underexplored in the literature. This article aims to identify and structure the relationships of logistic decisions to optimize total installation costs. A conceptual framework is proposed, detailing logistical decisions and their influencing factors. The results are based on a literature review and survey research for validation with specialists in logistics and offshore wind farms. The findings include the key decisions: port installation selection; vessel fleet selection; installation strategy selection; turbine pre-assembly method selection; aggregate planning approach; installation schedule coverage; storage strategy of components; and the degree of sharing information. The framework reveals the importance of coordinating the value chain in the installation process, mainly due to the influence of weather factors; the logistic decisions, when considered in a systemic view, can contribute to a global efficiency gain in the installation process.